Renal cell carcinoma: epidemiology, risk factors and clinicopathological profile (BIRDEM Medical Journal, 2025)
Background: The incidence of renal cell carcinoma (RCC) is increasing worldwide. The aims of this study were to describe epidemiological data, risk factors, clinicopathological characteristics of RCC. Methods: This cross-sectional descriptive study was carried out at the department of Urology, BIRDEM General Hospital from Janaury 2013 to July 2023. All radiological characteristics and fine needle aspiration (FNA) positive RCC cases were included and othere renal tumor such as angiolipoma, renal cyst, renal tuberculosis were excluded. Results: A total 200 RCC patients were included in the study. The mean age at presentation was 52.28 years and male (74%) were predominant. Most of the patients (66%) were asymptomatic, smoking (62%) was the most common modifiable risk factor, 50% patients had hypertension. In 54% cases right kidney was involved. Raised erythrocyte sedimentation rate was the most common (60%) paraneoplastic feature. The most common histopathologic type of renal tumour was clear cell carcinoma (70%), followed by papillary (20%) and chromophobe (6%) carcinoma; 66% of the patients presented at Robsing Stage II and 20% cases diagnosed as stage III. Conclusion: It had been observed that RCC mostly occurred in young male patient at right kidney with fewer symptomatic detection. Tobacco smoking were the most common modifiable risk factor. Diagnosis were made at advance stage of the disease.BIRDEM Med J 2025; 15(1): 16-21